(untitled) (Journal of the College of Basic Education, 2022)
The experiment was carried out to study variables ecological effect on growth and grain characters of two( bread wheat)IPA 99 and Abu Graib. The two genotype planted in date 16 th Oct,1 Nove , 16 th Nove and 1Dec. Using randomized completed block design, arranged split plot , three replicates were emplolyed . The results showed Abugarib dominated in plant height with increaic of 41%. IPA99 genotype gave highest growth rate weekly (4.97 mg)while gentypes AbuGraib gave alowest growth rate weekly (4.88 mg)The sowing date 16 th Oct gave alowest mean growth rate weekly for grain (5.87mg ).